NTT Develops a Smell-o-Phone. (IEEE spectrum)
Not content to serve only its customers' eyes and ears, Japan's NTT Communications, of Tokyo, has just finished testing an Internet-connected odor-delivery system to be used by retailers and restaurants to attract customers.